Pungutan Liar Pada Program Pendaftaran Tanah Sistematis Lengkap - Permadi, Iwan (Universitas Widya Gama Malang, 2024)
The acts of wild scrutiny against the PTSL program are clearly not based on clear legal rules except those which have been established in the SKB 3 ministers. The existence of long, complicated and exhausting procedures of service makes the public dependent and accustomed to dealing with corrupt public services, thus creating a tendency of the public to tolerate the practice of wild bullying. The study in this study focuses on the action of the complete systematic land registration program. The method of research used is the normative jurisprudence with the method of approaching legislative regulations and conceptual approaches. The results of the research showed that the practice of savage bribery against land registration activities and government strategic programmes was caused by the weakness of integrity and professionalism of the organizers of public briberies, the ineffectiveness of supervision of the government’s strategic programs in preventing the occurrence of acts of corruption and savage Bribery and the bad habits of the people who consider the process through which it is not easy so that culture provides a sum of money under the pretext of the processes quickly and improvised. Enforcement of the law can be done preventively by doing coordination between the police, local government, BPN and village government. Repressively enforcing is carried out with repression and punishment against the perpetrators of wild scourge measurably and consistently Together with the saber pungli team.